The Estimation of Ground Carbon Stock in The Tourist Forest Area Ngalau Indah Payakumbuh - Lily Rahmawati; Chairul chairul (Jurnal Biologi Universitas Andalas, 2022)
Ngalau Indah tourist area, Payakumbuh City has a forest area and potential carbon stock. The aim of this study was to find out about the total biomass and carbon stock in Ngalau Indah tourist area, Payakumbuh City. The study would be from November until February 2022. Retrieval of data collection for trees and sapling had done with the nun-destruction method and understorey and litter had done with the destruction method. Based on the data, trees have obtained 12 families, and 18 species, and saplings have obtained 13 families and 16 species. The total biomass was 92,440 ton/ha was included 91,313 tons/ha for tress, 1,012 ton/ha for sapling, 0,053 tons/ha for understories, and 0,062 tons/ha for litter. Carbon stock of trees was 42,917 tonC/ha, sapling was 0,476 ton/ha, understories was 0,024 tonC/ha, litter was 0,029 ton/ha and total carbon stock was 43,446 tonC/ha.